Broadband Direction Finding by Phase Correlation With Circular Time-Modulated Array Antennas - Xin Zhou; Yahong Liu; Jian Zhang; Dan Tong; Xiaoyong Yang (International Journal of Antennas and Propagation)
A broadband direction finding method based on circular time-modulated array antennas (TMAs) is proposed, which utilizes the principle of phase correlation interferometer by analyzing harmonic components to obtain the phase difference between array elements. The two-dimensional baseline characteristics of the circular array enable broadband unambiguous angle condition, significantly enhancing the direction finding accuracy. The impact parameters (including the number of antenna elements and element spacing) on direction finding performance are analyzed in detail by using numerical simulation. The experimental verification is carried out by designing a 7-element array antenna operating at 1–3 GHz. The proposed method effectively mitigates the systematic error as well as the interference from environmental factors, further enhancing the stability and reliability in practical applications.